Shoot and root interactions in intercropped wheat and clover - Dauro, D.; Mohamed-Saleem, M.A. (1995)
The effect of the interaction of shoots and roots of intercropped wheat (Triticum durum var. Boohai) and clover (Trifolium quartinianum A. Rich) on the dry matter yield of shoots and roots and on the seed yield of wheat and clover was studied in wooden boxes in the dry and wet seasons with and without N applied to wheat. Root interaction, but not shoot interaction, affected the yields of the two component crops significantly. The intermingling of clover roots with wheat roots increased wheat yield while reducing that of clover. An application of N fertilizer to wheat did not alter this relationship, although it increased wheat yield. Nitrogen increased wheat yield more in the presence of root interaction with clover than in its absence. Early competition for N reduced clover yield when both root systems interacted.